2012
DOI: 10.1016/j.jbtep.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Mental contamination: The perpetrator effect

Abstract: In order to test the proposition that imagining carrying out an unacceptable non-consensual act can evoke contamination-related feelings in the perpetrator, 4 connected experiments were carried out involving male students. The effects of the experimental procedure were enhanced by the introduction of a theme of betrayal which boosted the feelings of contamination and urges to wash. The non-consensual scenarios were followed by substantial increases in negative emotions, notably shame, disgust and guilt, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 13 publications
7
49
1
Order By: Relevance
“…These results demonstrate that the psychometric properties of the MPQ-J have been verified. In addition, the lack of a significant difference in female and male mean scores for both subscales of the MPQ-J supports Rachman et al's (2012) hypothesis that feelings of mental contamination can be found in both males and females. This is the first study conducted in an Asian culture to develop a scale for measuring mental contamination.…”
Section: Mpq-washing Mpq-ideationsupporting
confidence: 58%
“…These results demonstrate that the psychometric properties of the MPQ-J have been verified. In addition, the lack of a significant difference in female and male mean scores for both subscales of the MPQ-J supports Rachman et al's (2012) hypothesis that feelings of mental contamination can be found in both males and females. This is the first study conducted in an Asian culture to develop a scale for measuring mental contamination.…”
Section: Mpq-washing Mpq-ideationsupporting
confidence: 58%
“…Similarly, Schnall, Benton, and Harvey (2008) demonstrated that physical cleaning reduced the severity of participants' negative moral judgments. Furthermore, experimental work has indicated that it is possible to evoke feelings of mental contamination and washing behaviours in healthy students by asking them to image either receiving or perpetrating a non-consensual kiss ( Zysk, 2012). Research has shown that imagining a consensual kiss with a man described as immoral was enough to evoke feelings of mental contamination in health participants ) and that appraisal variables uniquely predict feelings of mental contamination ).…”
Section: Introductionmentioning
confidence: 99%
“…Mental contamination is theorized to emerge predominantly in response to mental events (e.g., thoughts, memories, images), or experiences involving negative human interactions such as violations of morality (e.g., sexual victimization or other violation), betrayal, or humiliation (Ishikawa, Kobori, & Shimizu, in press; Rachman, 2006, 2010; Rachman, Radomsky, Elliott, & Zysk, 2012). In contrast with contact contamination, sensations associated with mental contamination are typically described as diffuse, difficult to locate, with some individuals reporting feeling dirty “inside their bodies” or “under their skin” (Coughtrey Shafran, Lee et al, 2012).…”
mentioning
confidence: 99%
“…Second, collapsing this broad range of negative emotions into aggregate variables may result in loss of important information about specific emotional responses underlying mental contamination concerns. Other studies, including those reporting individual emotional responses (Rachman et al, 2012), have not examined correlations between affective variables and indices of mental contamination (Elliott & Radomsky, 2012; Ishikawa et al, in press). …”
mentioning
confidence: 99%